Role of the Madden-Julian Oscillation in the transport of smoke from Sumatra to the Malay Peninsula during severe non-El Nino haze events - Koplitz, S.N.; Mickley, L.J.; Jacob, D.J.; Marlier, Miriam E.; DeFries, Ruth S.; Gaveau, D.L.A.; Locatelli, Bruno; Reid, J.S.; Xian, P.; Myers, S.S. (American Geophysical Union, 2018)
In June 2013, the Malay Peninsula experienced severe smoke pollution, with daily surface particulate matter (PM) concentrations in Singapore greater than 350 μg/m3, over 2 times the air quality standard for daily mean PM10 set by the U.S. Environmental Protection Agency. Unlike most haze episodes in the Malay Peninsula in recent decades (e.g., the September 2015 event), the June 2013 haze occurred in the absence of an El Niño, during negative Indian Ocean Dipole conditions, with smoke carried eastward to the Peninsula from fires in the Riau province of central Sumatra. We show that June 2013 was not an exceptional event; inspection of visibility data during 2005–2015 reveals two other severe haze events in the Malay Peninsula (August 2005 and October 2010) occurring under similar conditions. Common to all three events was a combination of anomalously strong westerly winds over Riau province concurrent with late phases of the Real‐Time Multivariate Madden‐Julian Oscillation Index, during negative phases of the Indian Ocean Dipole. Our work suggests that identifying the meteorological mechanism driving these westerly wind anomalies could help stakeholders prepare for future non‐El Niño haze events in Singapore and the Malay Peninsula.